Mental illness and sleep disorders among women with gynecological problems - Ray M. Merrill; Dajeong Song (Journal of Psychosomatic Obstetrics and Gynecology)
This retrospective cohort study identifies differences between rates of selected mental illnesses and sleep disorders according to eight gynecological problems. Analyses utilize medical claims data for adult employees of a large corporation during 2017–2021. Women with a gynecological problem (most notably pain, endometriosis, pelvic inflammation and bleeding) are significantly more likely to experience mental illness. Several gynecological problems are also significantly associated with sleep disorders. Women with a gynecological problem (vs. none) are 50% more likely to have a mental health problem and 44% more likely to have a sleep disorder after adjusting for age, marital status, dependent children and year. The largest differences between higher (%) mental illness and sleep disorders appear for hyperplasia (6% vs. 45%), cancer (11% vs. 68%), pelvic inflammation (46% vs. 79%) and pain (79% vs. 43%), respectively. On the other hand, the rate of having one or more gynecological problems ranges from 7.1% for women with no mental illness or sleep disorder to 20.6% for women with schizophrenia. Understanding the association between gynecological problems, mental illness and sleep disorders can help clinicians more effectively identify and treat patients.